Por que Desobedecer? - Obrigação Política e Resistência: Uma leitura de Alessandro Passerin d'Entrèves - Pardo, Maísa Martorano Suarez (2013)
This study aims to investigate the possibility of understanding civil disobedience as a political duty. For this, we analyze the works of the Italian political philosopher Alessandro Passerin d'Entrèves. From the author's conception of the State, we analyze the relations of command and obedience in the state s structure and establish another approach to the problem of obedience to the laws using d Entrèves concept of 'political obligation'. Analyzing studies from Passerin d'Entrèves, Norberto Bobbio and Hannah Arendt, specifically about the legitimacy of civil disobedience and resistance, we try to answer the question: Why should we disobey? To enable the approach described above, we explore some classic problems of political philosophy and law, such as the notion of authority, the conflict between the concepts of legality and legitimacy and the definition of the state as a monopoly of force. In this sense, this research addresses some conflicts between great streams of western thought, as positivism and natural law, political science and philosophy, among others. From d Entrèves notion of political obligation it is possible to understand civil desobedience as a duty, especially in the democratic experiences.